Penerapan Hygiene Dan Sanitasi Di Hotel Grand Dafam Bella Ternate - Muliyadi Muliyadi; Muhlisa Muhlisa; Mustafa Mustafa (JURNAL KESEHATAN LINGKUNGAN: Jurnal dan Aplikasi Teknik Kesehatan Lingkungan, 2020)
Grand Dafam Hotel is a 4-star hotel located in the city of Ternate, North Maluku. The existence of this hotel influences on increasing the number of tourists in Ternate because it is a 4-star hotel at an affordable price. Objective: The purpose of this study was to determine the application of Hygiene and Sanitation at the Grand Dafam Bella Ternate Hotel. Methods: This research design uses observational design with descriptive methods. The sample of this study is the total population, namely environmental and building health, room/room health requirements, sanitation facilities, employees, and food and beverage services at the Grand Dafam Hotel, Ternate. Sampling uses a total sampling technique. Instruments such as observation sheets/inspection forms refer to minister of health regulation Number 80 of 1990 regarding hospitality sanitation requirements and the Director-General of PPM and PLP Decree No. 95 of 1991 concerning Assessment of Hotel Health Examinations. Results: The results showed that the five components studied all met the requirements by accumulation, but some things did not meet the requirements such as a non-permanent waste collection facility. Conclusion: The conclusion of this study is the Hotel Grand Dafam Bella Ternate has implemented Sanitation and Hygiene properly.